Cultural and individual diversity in mental health services: defining and assessing clinical competences - Moleiro, C.; Freire, J.; Pinto, N.; Roberto, S. (Transcultural, 2014)
One of the most significant challenges facing the provision of health care in present societies is the fact that it needs to be sensitive to the growing diversity of patients, their families and origins. This is particularly salient in mental health care given the fact that most models of etiology and treatment were not historically-rooted in such diversity. The present paper describes the work that our team has been developing in order to (i) provide culturally and individually diverse groups in Portugal an opportunity to voice their psychological health needs, experiences and expectations of sensitive health services; (ii) develop distinct methods for assessing individual and cultural diversity competences for mental health practitioners; and (iii) ultimately lead to the discussion and greater recognition of such specific competences. Thus, this paper will present a description of our project and the five studies that were developed (both with clinicians and clients/potential clients). Key findings are included, followed by a brief conclusion and implications for practice.